Tariffs and Subsidies with Price Competition and Integrated Markets: The Mixed Strategy Equilibria. - Venables, A (1994)
This paper analyzes trade policy in an integrated market in which two firms are price competitors. If tariff or export subsidies are in place, there is no equilibrium in pure strategies. The import tariffs and export subsidies give one firm a price advantage in one market. The effect of this is to reduce the incentive, usually a characteristic of price competition, to undercut prices. This reduction in the intensity of competition means that import tariffs may be overshifted and that an export subsidy raises consumer prices in both countries.